P6 Coronary CT angiography derived pericoronary inflammation and personalised cardiovascular risk prediction in the lipid clinic: beyond the calcium score. (21st September 2022) - Graby, J; Sellek, J; Khavandi, A; Loughborough, W; Hudson, BJ; Shirodaria, C; Downie, P; Antoniades, C; Rodrigues, JCL
Abstract : Objective: Dyslipidaemia promotes atherosclerosis, increasing the risk of premature major adverse cardiovascular events (MACE). Coronary artery calcium scoring (CACS) is currently first-line for imaging asymptomatic patients. We quantified the re-stratification of subclinical atherosclerosis burden in Lipid Clinic patients assessed with CACS vs CTCA vs pericoronary fat attenuation index (FAI) measurement of inflammation. Methods: Analysis of a prospectively maintained database of asymptomatic Lipid Clinic patients undergoing CACS and CTCA (May 2019 - December 2020). CACS-defined Agatston score categories were compared with (i) CTCA-derived Coronary Artery Disease - Reporting and Data System (CAD-RADS) grading of stenosis, including a modifier for high-risk plaque (HRP), and (ii) FAI analysis. Results: 45 asymptomatic patients (55±9 years, 49% female) were included. CTCA re-classified CAD severity vs CACS in 62% (28/45) patients (p=0.005). HRP features were observed in 31% (14/45) patients, including 23% (7/31) with a CACS ≤100. 19% (8/42) patients with FAI analysis had inflammation >75th percentile (any vessel) vs age- and sex-matched controls, including 22% (6/27) patients with a CACS ≤100. 71% (5/7) had CAD-RADS 0 or 1 and 43% (3/7) had HRP. High FAI was seen across all groups of CACS and CAD-RADS. The proportion with high FAI was higher in CAD-RADS 0 vs CAD-RADS 4, and CACS severity was not associated with level of inflammation (p=0.94). Conclusion: CTCA re-stratifies CAD presence and severity vs CACS in high-risk, asymptomatic patients. FAI provides incremental value in identification of patients at risk of future MACE regardless of CACS grade, including patients without evidence of overt CAD.